Online Voice Based Multipurpose Surveillance Robot for Defence Using Artificial Intelligence (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This project describes the design and construction of a multifunctional field monitoring robot for the detection of landmines, the detection of smoke and temperatures as well as the surveillance of gas quality in battling areas without providing any severe manual obstacles. Prediction of metals can be performed by land cognitive sensors, deadly gas attacks can occur and the robot can be remotely controlledvia an IOS device. The robot picks up sensor information and interfaces between the control unit and the robot with a microcontroller. The robot moves and lift everywhere on the basis of the input data from Android application. In this contemporary project is characterized by the integrated approach of Android's telephone and multiple IOT cloud services. All documentation on robot sensing devices is delivered to cloud servers and expressed on all devices. This allows the robot to monitor both usages, prefer military warfare and mining areas. This is a new attempt to integrate IOT and field robots into a massive design form. Specific design enhancements were an excellent choice for use and use in dangerous spots riddled with minefields and other hazardous pieces of metal.